Ageing Harlequin Duck Histrionicus histrionicus drakes using plumage characteristics - Smith, Cyndi; Cooke, Fred; Goudie, R Ian (Wildfowl, 1998)
Most ducks (Subfamily Anatinae) progress through a sequence of moults from natal downy plumage to definitive alternate plumage. The accurate identification of age classes by plumage allows the proportion of immature males to adult males in the autumn and winter populations to be used as an index of recruitment and to determine age-specific mortality. By observing Harlequin Ducks (tribe Mergini) that were banded as ducklings on streams in North America we show that males are distinguishable in the autumn of the hatch year. The Alternate I plumage is variable and could result from differences of up to 10 weeks in hatch date, or could reflect the physical condition of individual birds. We also show that males attain definitive alternate plumage after the pre-moult in the second calendar year. These plumage characteristics are useful both in the field and in working with specimens.